Strength and conditioning for sprint swimming. - Bishop, C.; Cree, J.; Read, P.; Chavda, S.; Edwards, M.; Turner, A. (Strength and Conditioning Journal, 2013)
Considerable improvements can be made from land-based strength and conditioning (s&c) for sprint swimming. The basis of training should aim to enhance performance, with particular focus on the start and turn, where the s&c coach can attempt to maximize ground reaction forces. The potential for injuries in both the lower and upper body should also be addressed, with specific attention on the knee and shoulder joints. Therefore, the purpose of this article was to provide s&c professionals with a review of existing literature surrounding the biomechanics of starts and turns and how its application can enhance swimming performance. For a video abstract of this article, see video, supplemental digital content 1, http://links.lww.com/scj/a130.